Representation of Existentialism in Jo Yong's Fairy Tales in the Drama It's Okay to Not Be Okay (A.J. Greimas Semiotic Analysis) - Syahrir, Hana Hanifah; Triarisanti, Risa; Widyana, Ashanti (CV. Rayyan Dwi Bharata, 2024)
This research examines the fairy tale 진짜 진짜 얼굴을 찾아서 (Finding The Real Face) which is found in the Korean drama